A review of hyperspectral imaging for nanoscale materials research. Issue 4 (21st April 2019) - Dong, Xingchen; Jakobi, Martin; Wang, Shengjia; Köhler, Michael H.; Zhang, Xiaoxing; Koch, Alexander W.
ABSTRACT: As an emerging technology, hyperspectral imaging (HSI), which combines both advanced spectroscopy and imaging techniques, provides sufficient information for spectral and spatial analysis and is thus suitable for distribution and property investigation of nanoscale materials. Considering the applications of HSI have spread from remote sensing to quality control of macro products such as food and milk, this article reviews recent research of HSI in a new field of nanoscale materials. On the basis of fundamental parts of a HSI system, new techniques fitting specifically for nanoscale materials imaging such as dark field and Raman spectroscopy are introduced. Nanoscale materials, including metal nanoparticles, carbon nanotubes and graphene, biological components in cells and tissues, as well as multi-layer nanoscale materials, are the research hotspots utilizing HSI technology. Related research reports of the above materials are reviewed based on the physical distinction of these nanoscale materials. It is believed that HSI technology is a strongly potential technique for property investigation and manipulation of nanomaterial for various applications.